2013
DOI: 10.1073/pnas.1220076110
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-driven collective interactions in DNA brushes on a biochip

Abstract: Cell-free gene expression in localized DNA brushes on a biochip has been shown to depend on gene density and orientation, suggesting that brushes form compartments with partitioned conditions. At high density, the interplay of DNA entropic elasticity, electrostatics, and excluded volume interactions leads to collective conformations that affect the function of DNA-associated proteins. Hence, measuring the collective interactions in dense DNA, free of proteins, is essential for understanding crowded cellular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 39 publications
3
88
0
1
Order By: Relevance
“…It was also observed that for C Spd > C * Spd , the collapsed domains were smaller in a denser brush of shorter chains, which is consistent with the prediction from our scaling argument R c ∼ N 0.4 σ −0.2 . The scaling relationship of R c ∼ N 0.4 σ −0.2 further explains the various size of octopus-like micelle domain depicted in (2), (4), (6) in Fig. 7.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It was also observed that for C Spd > C * Spd , the collapsed domains were smaller in a denser brush of shorter chains, which is consistent with the prediction from our scaling argument R c ∼ N 0.4 σ −0.2 . The scaling relationship of R c ∼ N 0.4 σ −0.2 further explains the various size of octopus-like micelle domain depicted in (2), (4), (6) in Fig. 7.…”
Section: Discussionmentioning
confidence: 55%
“…Double-stranded DNA brushes on a biochip [4] at a cell-like density (∼ 10 4 kb/µm 3 ) have been developed as a platform to study cell-free gene expression [5]. Due to the negative charges along the backbone, this synthetic system behaves like a well-defined strong polyelectrolyte brush [5], the height of which can be varied by modulating the ionic strength of monovalent salt (NaCl) solution and the grafting density [6]. Recently, it has been reported that trivalent counterions, spermidine 3+ (Spd 3+ ), can induce a collapse transition of DNA brush into fractal-like dendritic macroscopic domains [7].…”
mentioning
confidence: 99%
“…In the osmotic regime, a precondensed 3.5 kb brush extends to a height of ∼1 μm, which is well beyond the evanescent excitation length 31 and is therefore not measurable by TIRF. Condensation was triggered by adding a single aliquot of concentrated Spd solution ( Figure 1G and Movie S2).…”
Section: ■ Resultsmentioning
confidence: 99%
“…29 The brush was immersed in a low-salt solution (3 mM NaCl), an osmotic brush regime in which the osmotic pressure due to the confined ions induces maximal swelling of the brush up to the 1.2 μm chain contour length. 31 The Spd concentration (C Spd ) was incrementally increased by adding minute volumes of concentrated Spd solution to the reservoir. Passing 60 μM Spd initiated a major change in the surface fluorescence, which began with the emergence of a single bright spot surrounded by a ∼1 μm thick perimeter with reduced fluorescence ( Figure 1A and Movie S1 in the Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 99%
“…6,7,16,20 Although the distribution of DNA chain segments in DNA brushes has not been fully resolved, 16,17 we here use the Alexander approximation, which assumes that the local concentration of Kuhn segments is uniform in the brush region. 21 This treatment highlights the roles played by transcription for chromatin structures, rather than the details of brush models.…”
Section: Modelmentioning
confidence: 99%